Plant silicon defences reduce the performance of a chewing insect herbivore which benefits a contemporaneous sap‐feeding insect. (22nd July 2022) - Islam, Tarikul; Moore, Ben D.; Johnson, Scott N.
Abstract: Plant‐mediated interactions between phytophagous insects are ubiquitous. Silicon (Si) accumulation can defend plants against chewing insect herbivores, although sap‐feeders are comparatively less affected. It remains unknown how Si impacts interspecific interactions between chewing and sap‐feeding insect herbivores when sharing a host plant. We grew the model grass Brachypodium distachyon with (+Si) or without (−Si) Si and assessed the impacts of Si supplementation on the contemporaneous performance and interguild interactions between a chewing ( Helicoverpa armigera ) and a sap‐feeding ( Rhopalosiphum padi ) insect herbivore. We further performed dual‐choice tests to assess insect preferences for +Si or −Si plants with or without prior insect attack. Si reduced the relative growth rate (RGR) of both separately and contemporaneously fed caterpillars ( H. armigera ). Conversely, aphid abundance was higher on +Si plants compared to −Si plants. Caterpillar RGR and aphid abundance were negatively correlated on shared host plants. Furthermore, decreased caterpillar RGR on +Si plants benefitted aphid colonisation, indicating the plant‐mediated effects of Si on interspecific competition between the two insects. Attack by caterpillars induced leaf Si accumulation, regardless of aphid presence. In dual‐choice tests, caterpillars preferred aphid‐attacked −Si plants to aphid‐attacked +Si plants, whereas aphids preferred caterpillar‐attacked +Si plants to caterpillar‐attacked −Si plants. Our results provide the first evidence for plant‐mediated effects of Si on interspecific competition between two insect herbivores. We suggest that the dissimilar effects of Si against different feeding guilds of herbivores may promote asymmetry in interspecific competition when sharing host plants, potentially impacting insect abundance and distribution. Abstract : Silicon (Si) supplementation of plants reduced relative growth rates (RGRs) of Helicoverpa armigera caterpillars while promoting colonisation by aphids ( Rhopalosiphum padi ). Caterpillar RGR and aphid abundance were negatively correlated on contemporaneously shared host plants. Furthermore, decreased caterpillar performance on Si‐supplemented (+Si) plants benefitted aphid colonisation. In dual‐choice tests, aphids preferred caterpillar‐attacked +Si plants to caterpillar‐attacked Si‐free (−Si) plants, whereas caterpillars preferred aphid‐attacked −Si plants to aphid‐attacked +Si plants. Effects of plant silicon defences against chewing vs. sap‐feeding insects